PENGARUH PENGGUNAAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR APRESIASI SENI RUPA DI SMA NEGERI 1 CANDUANG - Dr. Ramalis Hakim, M.Pd., NITA INDAH SARI, Drs. Eswendi, M.Pd. (Serupa The Journal of Art Education, 2017)
This study aims to determine the effect of the use of contextual teaching and learning approach to the learning achievement of art appreciation of SMA Negeri 1 Canduang students. To know the achievement of the purpose of the research, conducted a quasi experiment research with nonrandomized control group pretest and posttest design.The research method used is Quasi Eksperimen. Samples taken by purposive random sampling technique with the number of samples of 42 people and divided into two classes, namely experimental class and control class. The data collected by using the instrument in the form of test, then the data is processed by using descriptive and comparative technique by utilizing SPSS version 16 program.The results obtained : First, the use of contextual teaching and learning approach can be applied in learning art appreciation. It is seen in the activities of students during the learning. In this usage can be seen from the result of student learning with Minimum Exhaustiveness Criterion (KKM) that is 76. Secondly, Based on hypothesis test tcount = 3.011 and ttable = 2,021. This means tcount > ttable. This means tcount > ttable , then Ho is rejected, meaning that the mean of the experiment class and control class values is not identical or different.Keywords : Contextual teaching and learning approach (CTL), student learning outcomes